Impact of Thermal Radiation on MHD Squeezing Flow of a Casson Fluid between Collateral Plates - Vadithya, Meenakshi; Naikoti, Kishan; Macha, Madhu (Discontinuity, Nonlinearity, and Complexity, 2026)
The present article mainly focuses on effect of thermal radiation on magneto hydrodynamic squeezing flow of Casson fluid between two equidistant plates. Non-linear partial differential equations of motion which are governing the flow are made non-dimensional by imposing similarity transformations. Runge-Kutta-Fehlberg scheme used here to solve these non-linear equations, by converting them into a set of initial value problem with single order. The velocity and temperature profile analysis has been carried out by taking into consideration of different parameters involved in it such as, squeeze number, magnetic number, Eckert number, radiation parameter, Prandtl number and Casson fluid parameter etc., and discussed them graphically in suitable manner such that interesting aspects of the solution can be adopted. And also, numerical results of nusselt number and skin friction co-efficient have been shown in this presentation. Velocity profile increases for increasing magnetic parameter near upper plate but it decreases near lower plate. Further same behavior observed for increasing squeeze number. Temperature profile increases with increasing magnetic parameter, radiation parameter and Casson fluid parameter but decreases with Eckert number.